Plan de comunicación interna del "Banco Corporativo Americano (BCA)" en el marco del COVID-19 - Lavandera Liria, Jorge Alberto (2020)
Banco Corporativo Americano faces one of the biggest challenges in history with the covid-19 outbreak. Through their internal communications area, the bank must design and implement a strategic plan that seeks to bring back the employees safely to the headquarters, protecting their health and keeping an optimal communication with the employees that are agency based nationwide that kept working during the entire pandemic as per usual.